Human Rights Violations: A Case Study of Palestine (2000-2024) - Warraich, Saqib Khan; Khan, Muslim; Ahmed, Umair (Pakistan Languages and Humanities Review, 2024)
Human rights have constantly been violated by Israel backed by America. It is crucial to address the violations to find solution for the issue. It has been commenced from the inception of Israel. However, in this paper, the time from 2000 to 2024 have been examined to provide accurate data and solution to a massive human rights violations in the region. Qualitative methodology and secondary sources have been used to understand the Palestine situation under the human rights theory. As a result, the state of Israel has further enhanced the brutality in the region. To a large extant women, and children have been perished. All these human rights violations have taken place owing to the support of America. In sum, human rights have massively been violated by Israel backed by the US. It shows they have nothing to do with democracy and human rights but selfish interest. Hence, the democratic principles must be redefined and defended by the globe regardless of any influence and discriminations.